Gastroenterology and liver disease - Aspinall, Richard J. (Mosby, 2002)
Featuring more than 300 full-color illustrations, Mosby's Color Atlas and Text -- Gastroenterology and Liver Disease presents comprehensive information on gastroenterology in a concise, easy to assimilate format. Key features include definition boxes, diagnostic and therapeutic algorithms, tables of comparative data and summary boxes. The emphasis throughout is on symptomatology, investigation, and treatment, guiding the reader through the correct processes to accurately diagnose and treat the full range of gastrointestinal conditions. The book is extensively illustrated throughout, featuring full-color clinical and endoscopic photographs, the very latest black-and-white imaging modalities, numerous definition boxes and tables, and full-color algorithms and artwork